The coastal environmental profile of Lingayen Gulf, Philippines. - Edited by Liana T. McManus and Chua Thia-Eng. (Manila, Philippines ICLARM, 1990)
ICLARM Technical Reports; 22ICLARM Contribution No. 514Association of Southeast Asian Nations/United States Coastal Resources Management Project Technical Publications Series 5
Keywords: Renewable natural resources; Environmental policy; Coastal zone management; Coastal environmental